Advances in reactive air wetting and brazing of engineering ceramics - Mingfen Zhang; Shunjian Xu; Fabrizio Valenza; Xiangzhao Zhang; Guiwu Liu; Guanjun Qiao (Journal of Advanced Ceramics)
The reactive air brazing (RAB) process of ceramics was developed in the early 2000s because high-temperature electrochemical devices, such as solid oxide fuel cells (SOFCs), gas separators, reformers, and ion transport membrane systems, are increasingly emerging. Accordingly, the reactive air wetting (RAW) and RAB of oxide ceramics have been investigated. Starting from the introduction of the advantages of the RAB process, the thermal expansion coefficients (TECs) of related materials, and the estimation of the TECs of Ag-based composite fillers, the RAW and RAB of ceramics are reviewed by classifying the employed ceramic materials, which mainly include yttria-stabilized zirconia (YSZ), perovskite oxides, Al2O3, and nonoxide ceramics. In particular, the RAW and RAB processes, interfacial microstructures, reaction products, and joint reliability (including joint strength, fracture energy, gas tightness, and high-temperature aging resistance) are highlighted for understanding interfacial behavior and joint performance and developing application-oriented brazing technology. Finally, some helpful conclusions are drawn after summarizing the RAB of oxide ceramics. The prospects for RAB of SiC and high-entropy oxide ceramics are proposed after summarizing the RAB of oxide and nonoxide ceramics, and several aspects are proposed for promoting the development and application of RAB technology.